IMPROVING READING COMPREHENSION SKILLS WITH COOPERATIVE APPROACH TYPE CIRC - Widyana Cahyaning Gerhastuti; Pratiwi Pujiastuti; Anwar Novianto (Indonesian Journal of Elementary Teachers Education, 2021)
This study aims to improve the learning process and the results of reading comprehension skills with the CIRC learning model for fifth grade students of SD Negeri Kotagede 5 Yogyakarta. This type of research is classroom action research with the Kemmis and Mc Taggart model. The subjects of this study were the fifth grade students of SD Negeri Kotagede 5 Yogyakarta totaling 27 students. Data were collected by using observation, test, and documentation techniques. The data analysis technique is descriptive quantitative. The results showed that there was an increase in the learning process and the results of reading comprehension skills with the CIRC type cooperative approach. In the pre-action, the average value of the students' reading comprehension skills class was 68.94 with a percentage of completion of 44.44%, then in the first cycle it increased to 81.48 with a complete percentage of 75.73%, and increased again in the second cycle to 86.15 with a complete percentage of 100 %.